HUBUNGAN PENGETAHUAN PENCEGAHAN KEPUTIHAN DENGAN PERILAKU REMAJA PUTRI TENTANG PERSONAL HYGIENE DI SMA N 5 BATAM - Mariyana, Mariyana; Adila, Adila (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
According to WHO data, vaginal discharge affects about 50% of the female population and affects almost all ages. Based on the pre-survey on March 24, 2015, there were 6 female teenage girls who did not know how to prevent vaginal discharge, and 4 female students knew how to prevent vaginal discharge. The purpose of this study was to determine the relationship between knowledge of vaginal discharge prevention and personal hygiene behavior at SMA N 5 Batam in 2015. The design of this study used a cross-sectional study, Research Time 08 May 2015, the place of research was SMA N 5 Batam, the research population was all XI students. at SMA N 5 Batam the research sample was 128 people, the sampling technique was random sampling, the data collection tool used a questionnaire, the data collection technique in this study was primary data by distributing questionnaires directly to respondents, univariate and bivariate analysis using the chi-square test. based on the results of research that has been done that there is a relationship between knowledge of prevention of vaginal discharge with personal hygiene behavior in SMA N 5 Batam by giving a questionnaire. In order to be able to maintain and increase efforts in providing health knowledge about the cleanliness of genital organs to students so as to avoid the occurrence of vaginal discharge